1984
DOI: 10.1159/000194707
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Peak Expiratory Flow Rate as a Prognostic Index in Asymptomatic Asthma

Abstract: The prognostic relevance of an enhanced variability of peak expiratory flow rate (PEFR) throughout the day was evaluated in asthmatics in remission: it was expressed as the coefficient of variation (CV) of values recorded 4 times daily for weeks. Outcome at 3, 6, and 12 months was assessed in 2 groups of 16 patients each, differing because of a CV respectively higher (group A) and lower (group B) than 8%. A significantly higher frequency of abnormal PEFR values during the subsequent months was recorded in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Such data are consistent with the results of Sont and coworkers,54 who showed improved asthma control if bronchial reactivity tests were used to guide asthma treatment. PEF monitoring reduces unscheduled doctors’ visits in adults,55 and PEF variation after bronchodilator response has been proven to be related to admission rates in adults and children 44,56,57. However, lung function deterioration and exacerbation risks are not always closely associated in children; Fuhlbrigge and colleagues51 reported that even children who had normal values of lung function had exacerbations.…”
Section: Classic Methods Of Assessment Of Asthma Control and Severitymentioning
confidence: 99%
“…Such data are consistent with the results of Sont and coworkers,54 who showed improved asthma control if bronchial reactivity tests were used to guide asthma treatment. PEF monitoring reduces unscheduled doctors’ visits in adults,55 and PEF variation after bronchodilator response has been proven to be related to admission rates in adults and children 44,56,57. However, lung function deterioration and exacerbation risks are not always closely associated in children; Fuhlbrigge and colleagues51 reported that even children who had normal values of lung function had exacerbations.…”
Section: Classic Methods Of Assessment Of Asthma Control and Severitymentioning
confidence: 99%
“…Spirometric measures of lung function are not easily obtainable in certain clinical settings and/or geographic areas, and thus, although controversial [31], peak expiratory flow (PEF) has been proposed as a surrogate measure of FEV 1 [32]. Thamrin et al .…”
Section: Predicting Asthma Exacerbationsmentioning
confidence: 99%
“…While it is well established that variation in airway function is a central feature of the disease, this is largely based on longterm variability of airway obstruction from several diurnal measurements of FEV1 and peak expiratory flow rate (PEFR) over several weeks or months of measurement [32,33]. Indeed, high diurnal variation of PEFR is associated with a higher risk for exacerbation [32].…”
Section: Variation In Rrsmentioning
confidence: 99%
“…Indeed, high diurnal variation of PEFR is associated with a higher risk for exacerbation [32]. Long-term variation has also been assessed by FOT showing that within-day and between-day variability in Rrs is elevated in asthma [34].…”
Section: Variation In Rrsmentioning
confidence: 99%